DESCRIPTIVE AND IMPACT OF DYSMENORRHEA ON UNIVERSITY STUDENTS - Utami, Fauzia Kartika; Khoiriyah, Wirdah Nur; Yuhakky, Falziya; Nisa, Hoirun (Journal of Maternity Care and Reproductive Health, 2024)
Dysmenorrhea is a condition of pain or cramps in the lower abdomen, hips, waist, thighs and calves that occurs during menstruation. The prevalence of dysmenorrhea in Indonesia reached 64.25%, with 54.89% of them being primary dysmenorrhea and 9.36% secondary dysmenorrhea. Therefore, the high number of dysmenorrhea experienced by female students requires appropriate treatment regarding dysmenorrhea in female students. This research aims to determine the description and impact of dysmenorrhea on Jabodetabek students. The research design used was cross sectional with a purposive sampling technique and involved 226 respondents. Data was collected using a questionnaire adapted from a standard questionnaire. Data analysis was carried out using the Chi Square test. The results of the analysis showed that 62.8% of respondents experienced mild dysmenorrhea and 37.2% experienced severe dysmenorrhea. There is a statistically significant relationship between impaired learning concentration (p<0.001; OR: 1.78; 95% CI: 1.50 - 2.12), impaired physical activity (p <0.001; OR: 2.30; 95% CI: 1.85 - 2.87), and stress (p<0.001; OR: 1.47; 95% CI: 1.29 - 1.68) with the severity of dysmenorrhea. Further education is needed regarding the management of dysmenorrhea, both through pharmacological and non-pharmacological therapy to minimize the various impacts that can occur. This research can also be used as educational material regarding dysmenorrhea